Radio-frequency triggered heating and drug release using doxorubicin-loaded LSMO nanoparticles for bimodal treatment of breast cancer - Kulkarni, Vaishnavi M.; Bodas, Dhananjay; Dhoble, Deepa; Ghormade, Vandana; Paknikar, Kishore (Colloids and Surfaces B-Biointerfaces, 2016)
Radio-frequency responsive nanomaterials combined with drugs for simultaneous hyperthermia and drug delivery are potential anti-cancer agents. In this study, chitosan coated La0.7Sr0.3MnO3 nanoparticles (C-LSMO NPs) were synthesized and characterized by X-ray diffraction, dynamic light scattering, Fourier transform infra red spectroscopy, vibrating sample magnetometer, scanning electron and atomic force microscopy, Under low radio-frequency (365 kHz, RF), C-LSMO NPs (90 nm) showed good colloidal stability (+22 mV), superparamagnetic nature (15.4 emu/g) and heating capacity (57.4W/g SAR value). Chitosan facilitated doxorubicin entrapment (76%) resulted in DC-LSMO NPs that showed drug release upon a 5 min RF exposure. MCF-7 and MDA-MB-231 cancer cells responded to a 5 min RF exposure in the presence of bimodal DC-LSMO NPs with a significant decrease in viability to 73% and 88% (Pearson correlation, r = 1, P<0.01) respectively, as compared to hyperthermia alone. Internalization of DC-LSMO NPs via the endosomal pathway led to an efficient localization of doxorubicin within the cell nucleus. The ensuing DNA damage, heat shock protein induction, and caspase production triggered apoptotic cell death. Moreover, DC-LSMO NPs successfully restricted the migration of metastatic MDA-MB-231 cancer cells. These data suggest that DC-LSMO NPs are potential bimodal therapeutic agents for cancer treatment and hold promise against disease recurrence and drug resistance. (C) 2016 Elsevier B.V. All rights reserved.